2019
DOI: 10.29333/iji.2019.12123a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mathematical Disposition on Mathematical Power Formation: Review of Dispositional Mental Functions

Abstract: This study applied mixed methods with concurrent triangulation design that combines quantitative and qualitative research method in a balanced manner and convergence. Population in this study was as 188 students of 8th grade in a state junior high school in Semarang City, Indonesia. By using purposive sampling technique, 60 students were selected as the research subjects. The study aimed to observe the effect of mathematical disposition on students' mathematical power ability, and to describe how dispositional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 9 publications
(9 reference statements)
1
29
0
6
Order By: Relevance
“…Based on the results of data analysis it was concluded that mathematical disposition and student learning motivation had a significant influence on problem solving abilities, it could see from the double regression equation: ̂ . This is in line with the research of Darmawati (2017), Fadila, Septiana, Amelia, & Wahyuni (2019), Kusmaryono, Suyitno, Dwijanto, & Dwidayati (2019) and Taiyeb & Mukhlisa (2015), that there were a relationship between mathematical disposition, learning motivation and learning outcomes. Likewise, it is also in line with the research of Huda (2016) and Ningsih & Rohana (2016) that mathematical dispositions and student learning motivation are mainly students' activeness in aspects: working together to solve problems, giving opinions when there are group friends who have not understood, resolved dissent, and communicated with friends and teachers during the learning process in the classroom has increased.…”
Section: Enoughsupporting
confidence: 91%
“…Based on the results of data analysis it was concluded that mathematical disposition and student learning motivation had a significant influence on problem solving abilities, it could see from the double regression equation: ̂ . This is in line with the research of Darmawati (2017), Fadila, Septiana, Amelia, & Wahyuni (2019), Kusmaryono, Suyitno, Dwijanto, & Dwidayati (2019) and Taiyeb & Mukhlisa (2015), that there were a relationship between mathematical disposition, learning motivation and learning outcomes. Likewise, it is also in line with the research of Huda (2016) and Ningsih & Rohana (2016) that mathematical dispositions and student learning motivation are mainly students' activeness in aspects: working together to solve problems, giving opinions when there are group friends who have not understood, resolved dissent, and communicated with friends and teachers during the learning process in the classroom has increased.…”
Section: Enoughsupporting
confidence: 91%
“…According to Kemendikbud (2016) the affective domain determines a person's learning success. This is in line with Kusmaryono, Suyitno, Dwijanto, & Dwidayati, 2019;Lin & ChunTai (2016) teacher need to focus not just on the development of math knowledge and skills, but on the development of the mathematics disposition and also should optimize the dispositional mental functions of the students by selecting a learning model, affective and conative. Mathematical disposition is, therefore, strong willingness, awareness, dedication, and tendency of a student to think and act mathematically in a positive manner (Akbar, Hamid, Bernard, & Sugandi, 2017).…”
Section: Introductionmentioning
confidence: 65%
“…However, after the scaffolding implementation, all factors of mathematics anxiety decreased significantly. The scaffolding gave to students to reflect their work and led them to initial knowledge to solve problems they had [10] and also improved positive disposition toward mathematics [16], [23].…”
Section: Figure 3 Student (S3) Answer After Scaffoldingmentioning
confidence: 99%